The Impact of Environmental Taxation on Corporate Financial Performance : Evidence from ASEAN Countries (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study examines the impact of environmental taxation on corporate financial performance across ASEAN countries. Environmental taxation has become an essential policy instrument for addressing environmental concerns and promoting sustainable development. However, its implications for corporate financial performance remain debated. Using panel data from various sectors in ASEAN countries, this research investigates the relationship between environmental tax policies and key financial indicators, including profitability, return on assets, and market value. The findings reveal that environmental taxation can have both positive and negative effects, depending on the industry, tax structure, and corporate adaptability. Companies that invest in green innovation and sustainable practices tend to experience improved financial performance in the long run, suggesting that environmental taxation can act as a catalyst for corporate sustainability. The study provides insights for policymakers and business leaders on balancing environmental goals with economic competitiveness in the ASEAN region.